Meningkatkan Kemampuan Bahasa Inggris Mengenai Materi Animals Melalui Media Pembelajaran Flashcard - Nanda Ramadani; Mei Vina Estetika; Anggia Aldwi Adisti; Ezra Imamat Sihombing; Halimatus Azizah Hutasuhut; Immanuel Hasiholan Siregar (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This research aims to increase student’s understanding of animal vocabulary materials in learning English in elementary school through the use of flashcard media. The method used in this research is a qualitative approach with interview and observation techniques. Research results show that the use of flashcards as learning media can increase student involvement and motivation in the learning process. Students show a significant improvement in recognising animal names, characteristics, sounds and meanings in English after learning using flashcards. Observations during learning activities show that students are more active and enthusiastic, especially when playing flashcards in groups. This finding indicates that flashcards not only function as a visual aid, but also create a fun and interactive learning atmosphere. Thus, the use of flashcards in Learning English Language in elementary school can be an effective strategy to increase student’s understanding of the material taught.